2019
DOI: 10.1007/s40830-019-00253-2
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Parent Phase Compliance on the Fatigue Lifetime of Ni–Ti

Abstract: It has been previously suggested that the fatigue lifetime of superelastic Ni-Ti might be improved if the R-phase were the parent to martensite rather than austenite. This body of work tests that hypothesis in two separate side-by-side fatigue tests both carefully constructed to match the superelastic properties in the two study arms. Both experiments show the R-phase parent to be more durable than the more commonly considered austenitic parent phase. The first experiment considers straight wire specimens fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[ 2,4 ] Recent studies have even shown that the R‐phase, acting as the parent phase in the transformation to B19′ improves the fatigue lifetime of superelastic NiTi. [ 5 ] The R‐phase, like martensite can detwin, reorient, and undergo a thermal or stress induced transformation. [ 6–8 ] For these reasons, it is difficult from ordinary macroscopic measurements to decouple elastic and inelastic contributions (from their respective phases) to the overall deformation.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 2,4 ] Recent studies have even shown that the R‐phase, acting as the parent phase in the transformation to B19′ improves the fatigue lifetime of superelastic NiTi. [ 5 ] The R‐phase, like martensite can detwin, reorient, and undergo a thermal or stress induced transformation. [ 6–8 ] For these reasons, it is difficult from ordinary macroscopic measurements to decouple elastic and inelastic contributions (from their respective phases) to the overall deformation.…”
Section: Figurementioning
confidence: 99%
“…Therefore, the presence of the intermediate R‐phase, during the stress induced phase transformation between B2 and B19', has implications for extending the fatigue lifetime of superelastic devices (e.g., as was recently demonstrated macroscopically in ref. [ 5 ] in which the intermediate R‐phase acts as the parent phase in phase transformation to B19').…”
Section: Figurementioning
confidence: 99%
“…During the subsequent lifetime, those implants are subjected to in vivo cyclic loadings, which lead inevitably to questions of fatigue damages. Minimizing the risks of fatigue failure and pushing the tolerable loads to increase the fatigue lifetime were targeted not only by various studies on structural optimization or optimization of manufacturing processes [1][2][3][4], but also by numerous studies on the material properties (e.g., [5][6][7][8]). In the scope of the latter studies, fatigue damages and their initiation were primarily attributed to local load peaks at structural imperfections in Nitinol [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%